Community psychology: Panic or panacea - Seedat, Mohammed; Cloete, Nico; Shochet, Ian (PINS-Psychology in Society, 2025)
The growing social upheaval and intensifying tensions in South Africa have by their very nature evoked concern and panic among mental health professionals. In an attempt to alleviate the concomitant anxiety and appear to be more responsive to the majority, many psychologists have boarded the community psychology wagon to cross the great divide between the comfortable consultancy room and the masses. In assessing whether community psychology is the appropriate vehicle for crossing the rubicon, we will start with an overview of different models of community psychology focusing on their different conceptualizations of mental illness and how each model sees the role of the psychologist in the context of psycho-social change.